Cytokine profiles in early rejection following OKT3 treatment in liver transplant patients. Issue 3 (2000) - Roayaie, Sasan; Sheiner, Patricia A.; Emre, Sukru; Guy, Steven; Schwartz, Myron E.; Boros, Peter; Miller, Charles M.
Abstract : OKT3, a murine monoclonal antibody specific to the human CD3 complex, induces immunosuppression by depletion of T cells. Administration of OKT3 results in significant release of proinflammatory cytokines, such as TNFα and IL1β. Liver recipients who experience rejection within 3 weeks after transplantation with OKT3 prophylaxis recover their T cells by postoperative day 10 despite complete initial clearance. We sought to analyze the role of proinflammatory and Th-1 cytokines in T cell recovery and rejection after liver transplantation with OKT3 prophylaxis. In plasma samples from 32 patients, we measured TNFα, IL1β, and IL6 (before transplant and on postoperative days 1, 2 and 3) and IL2, IFNγ, sIL2R and sICAM (postoperative days 5, 7 and 10) and examined possible correlations with T-cell recovery and occurrence of rejection within 3 weeks. TNFα, IL1β, and IL6 did not correlate with T-cell recovery. In patients who rejected, IL2 and IFNγ on postoperative days 5 and 7 correlated with degree of T-cell recovery by day 10; a significant rise in sIL2R over time also correlated with T-cell recovery in this group. ur results emphasize the role of Th-1 cytokines in rejection following OKT3 induction and suggest that markers of T cell activation may predict risk.